FAKTOR – FAKTOR YANG MEMPENGARUHI PENDAPATAN UMKM DI KECAMATAN TANJUNG PRIOK JAKARTA UTARA (STUDI KASUS BINAAN JAKPRENEUR) - Siti Mariam; Findy Yuliani (JURNAL LENTERA BISNIS, 2022)
This study aims to examine and analyze "The effect of business capital, skills training and information technology on MSME income (Case Study of MSMEs fostered by Jakpreneur )". The results of this study used purposive sampling method. The number of samples in this study amounted to 92 people. The dependent variable in this research is the income of MSMEs while the independent variables are business capital, skills training and information technology. This study uses a quantitative approach. The results of this study indicate that partially (t test) Business Capital (X1) has a positive effect on Income (Y) supported by the value of tcount > ttable (4.540 > 1.987) and the significance level is 0.000. Partially (t test) Skills Training (X2) has a positive effect on Income (Y) supported by the value of tcount > ttable (8.024 > 1.987) and the significance level is 0.000. Partially (t test) Information Technology (X3) has a positive effect on Income (Y) supported by the value of tcount > ttable (4.984 > 1.987) and the significance level is 0.000. Simultaneously (f test) Business capital (X1), Skills Training (X2) and Information Technology (X3) have a positive effect on Income (Y) with a value of fcount > ftable (29.456 > 2.71) with a significant value of 0.000 < 0.05 . The magnitude of the influence of Business Capital, Skills Training and Information Technology on Income is 50.1% while the remaining 49.9% is influenced by other variables not examined in this study.Keywords : Venture capital, skills training, information technology and MSME incomeÂ